The SAGE handbook of environmental change. Volume I Approaches, evidences and causes - Matthews, John A. (John Anthony) 1947-.; SAGE Knowledge (Online service). (London SAGE, 2012)
In more than 40 chapters, this work examines the historic importance and future development of the field of environmental change, including theory, research and practice.
Includes bibliographical references and index.
Keywords: Global environmental change; Electronic books